Impact of MAPK Pathway Activation in BRAFV600 Melanoma on T Cell and Dendritic Cell Function - Ott, Patrick A.; Bhardwaj, Nina (Frontiers in Immunology, 2013)
Constitutive upregulation of the MAPK pathway by a BRAFV600 mutation occurs in about half of melanomas. This leads to increased oncogenic properties such as tumor cell invasion, metastatic potential, and resistance to apoptosis. Blockade of the MAPK pathway with highly specific kinase inhibitors induces unprecedented tumor response rates in patients with advanced BRAFV600 mutant melanoma. Immune checkpoint blockade with monoclonal antibodies targeting CTLA-4 and PD-1/PD-L1 has also demonstrated striking anti-tumor activity in patients with advanced melanoma. Tumor responses are likely limited by multiple additional layers of immune suppression in the tumor microenvironment. There is emerging preclinical and clinical evidence suggesting that MAPK inhibition has a beneficial effect on the immunosuppressive tumor microenvironment, providing a strong rationale for combined immunotherapy and MAPK pathway inhibition in melanoma. The T cell response has been the main focus in the studies reported to date. Since dendritic cells (DCs) are important in the induction of tumor-specific T cell responses, the impact of MAPK pathway activation in melanoma on DC function is critical for the melanoma directed immune response. BRAFV600E melanoma cells modulate DC through the MAPK pathway because its blockade in melanoma cells can reverse suppression of DC function. As both MEK/BRAF inhibition and immune checkpoint blockade have recently taken center stage in the treatment of melanoma, a deeper understanding of how MAPK pathway inhibition affects the tumor immune response is needed.